2021
DOI: 10.1155/2021/7004798
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Study of Zuojin Pill in Relieving 1-Methyl-3-nitro-1-nitrosoguanidine-Induced Chronic Atrophic Gastritis

Abstract: The classic prescription Zuojin Pill (ZJP) shows a good therapeutic effect on chronic atrophic gastritis (CAG); it is of great significance to clarify its specific mechanism. Therefore, we explore the mechanism of ZJP on MNNG-induced CAG by integrating approaches. First of all, through the pathological changes of gastric tissue and the expression level of PGI and PGI/II in serum, the expression of inflammation-related factors was determined by RT-PCR to determine the efficacy. Then, UPLC-Q-TOF/MS was used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…CR-EF, with a ratio of 6:1, has been used in China for a long time to treat gastrointestinal diseases, especially chronic atrophic gastritis, gastric injury, acute gastric lesions and ulcerative colitis (UC) ( Figure 3 ). Many studies have shown that ZJP can treat chronic atrophic gastritis mainly by improving gastric histomorphology and gastric tissue inflammatory lesions ( Tong et al, 2021a ; Tong et al, 2021b ; Wen et al, 2022 ). Additionally, it can alleviate gastric injury by ameliorating the inflammatory infiltration of gastric tissue ( Wei et al, 2021a ).…”
Section: Main Herb Pairs Containing Coptidis Rhizomamentioning
confidence: 99%
“…CR-EF, with a ratio of 6:1, has been used in China for a long time to treat gastrointestinal diseases, especially chronic atrophic gastritis, gastric injury, acute gastric lesions and ulcerative colitis (UC) ( Figure 3 ). Many studies have shown that ZJP can treat chronic atrophic gastritis mainly by improving gastric histomorphology and gastric tissue inflammatory lesions ( Tong et al, 2021a ; Tong et al, 2021b ; Wen et al, 2022 ). Additionally, it can alleviate gastric injury by ameliorating the inflammatory infiltration of gastric tissue ( Wei et al, 2021a ).…”
Section: Main Herb Pairs Containing Coptidis Rhizomamentioning
confidence: 99%
“…CR-EF, with a ratio of 6:1, has been used in China for a long time to treat gastrointestinal diseases, especially chronic atrophic gastritis, gastric injury, acute gastric lesions and ulcerative colitis (UC) (Figure 3). Many studies have shown that ZJP can treat chronic atrophic gastritis mainly by improving gastric histomorphology and gastric tissue inflammatory lesions (Tong et al, 2021a;Tong et al, 2021b;Wen et al, 2022). Additionally, it can alleviate gastric injury by ameliorating the inflammatory infiltration of gastric tissue (Wei et al, 2021a).…”
Section: Effects On the Gastrointestinal Diseasesmentioning
confidence: 99%